Living Transcription: The Poetry of Jean Tortel - Suzanne Nash (Studies in 20th & 21st Century Literature, 1989)
With the publication of six new books of poetry since 1979, Jean Tortel has joined his contemporaries, Francis Ponge and Guillevic, as one of France's leading materialist poets. His writing, recounting the process of its own unfolding with voluptuous precision, is meant to bear witness through its figurations to the forces of chance and mutability governing the natural order. As such it constitutes a place of passage or verbal garden, both sumptuous and ordinary, where reading and formulation merge.
Keywords: poetry; 1979; Jean Tortel; Francis Ponge; Guillevic; France; materialist; poets; chance; mutability; natural order; verbal garden; garden; sumptuous; ordinary; reading; formulation